MEK Inhibition Targets Cancer Stem Cells and Impedes Migration of Pancreatic Cancer Cells In Vitro and In Vivo - Karolin Walter; Kanishka Tiwary; Marija Trajkovic-Arsic; Ana Hidalgo-Sastre; Laura Dierichs; Sven T. Liffers; Jiangning Gu; Johann Gout; Lucas-Alexander Schulte; Jan Münch; Thomas Seufferlein; Bruno Sainz; et al. (Stem Cells International)
Pancreatic ductal adenocarcinoma (PDAC) remains a devastating disease with a very poor prognosis. At the same time, its incidence is on the rise, and PDAC is expected to become the second leading cause of cancer-related death by 2030. Despite extensive work on new therapeutic approaches, the median overall survival is only 6-12 months after diagnosis and the 5-year survival is less than 7%. While pancreatic cancer is particularly difficult to treat, patients usually succumb not to the growth of the primary tumor, but to extensive metastasis; therefore, strategies to reduce the migratory and metastatic capacity of pancreatic cancer cells merit close attention. The vast majority of pancreatic cancers harbor RAS mutations. The outstanding relevance of the RAS/MEK/ERK pathway in pancreatic cancer biology has been extensively shown previously. Due to their high dependency on Ras mutations, pancreatic cancers might be particularly sensitive to inhibitors acting downstream of Ras. Herein, we use a genetically engineered mouse model of pancreatic cancer and primary pancreatic cancer cells were derived from this model to demonstrate that small-molecule MEK inhibitors functionally abrogate cancer stem cell populations as demonstrated by reduced sphere and organoid formation capacity. Furthermore, we demonstrate that MEK inhibition suppresses TGFβ-induced epithelial-to-mesenchymal transition and migration in vitro and ultimately results in a highly significant reduction in circulating tumor cells in mice.